Impact of Human Development Indicators on the losses caused by natural disasters in South Asian Countries: A panel data analysis - Tasnim, Rijwana (Brac University, 2023)
This thesis is submitted in partial fulfillment of the requirements for the degree of Master of Science in Applied Economics, 2022.